COVID-19: Mental Health Prevention and Care for Healthcare Professionals - Rolling, Julie; Mengin, Amaury C.; Palacio, Cédric; Mastelli, Dominique; Fath, Morgane; Gras, Adrien; Von Hunolstein, Jean-Jacques; Schröder, Carmen M.; Vidailhet, Pierre (Frontiers in Psychiatry, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic exposed health professional to high levels of stress inducing significant psychological impact. Our region in France, Grand Est, was the most impacted. In this context, we created CoviPsyHUS, a local mental health prevention and care system specifically dedicated to healthcare workers affected by the COVID-19 pandemic in one of this region tertiary hospital. CoviPsyHUS was gradually deployed in 1 month. To date, CoviPsyHUS comprises 60 mental health professionals dedicated to 4 complementary components: i) a medico-psychological hotline (170 calls), ii) relaxation rooms (used by 1,685 healthcare workers with 110 therapeutic workshops offered), iii) mobile teams (1,200 consultations with healthcare staff) and iv) a section dedicated to patients and their families. Among the key points to integrate into a crisis mental health care system we have identified: i) massive dissemination of medico-psychological support information with multimodal communication, ii) clear identification of the medico-psychological system, iii) proactive mobile teams to identify caregivers in difficulty, iv) concrete measures to relieve the healthcare professionals under pressure (e.g. relay in communication with families), v) support for primary needs (body care (physiotherapy), advice and first-line therapy of management of sleep disturbances) and vi) psychoeducation and emotion management techniques. The different components of CoviPsyHUS are key elements strictly meeting the needs of caregivers in crisis situations to manage ongoing stress mechanisms. The organization of these components, rapidly deployable and effective, make CoviPsy an innovative, reactive and transposable mental health prevention and care system that could serve as a universal and modular support model that can be deployed for other teams and countries affected by COVID-19 or similar exceptional health crises in the future.